Continuous magnetic pulsations (Pc3) dependency to the solar wind speed and dynamic pressure in 2007: article / Noradzmi Nasaruddin - Nasaruddin, Noradzmi (2013)
This study measures the dependency of Continuous Pulsations (Pc3) amplitude to the solar wind speed and dynamic pressure at the low latitude station Langkawi (LKW), Malaysia. To shows dependency, 10 days of wind data are collected in 2007 for having fastest and slowest wind speed. The Pc3 measured on the selected day’s shows that the wind speed above 600 km/s produces higher Pc3 amplitude. The mean amplitude for the fast wind speed is 0.1267nT, while wind speed below 300km/s produces lower Pc3 amplitude with the mean of 0.0835nT. On the other hand, the change of dynamic pressure shows a change of Pc3 amplitude. According to the obtained result, the solar wind dynamic pressure must be related to the change of Pc3 amplitude.